PERBANDINGAN PEMBELAJARAN METODE DRILL DAN KOMANDO DALAM SERVICE PENDEK BULU TANGKIS SISWA DI SEKOLAH DASAR - Endrawan, I Bagus; Satria, M. Haris (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2020)
This study was an experimental study that aims to determine the application method and the method of command drill results in short service badminton game. The subjects were fifth grade students of State Elementary School. Data collection techniques using the